Changes in Interstate Banking Laws: The Impact of Shareholder Wealth. - Black, Harold A; Fields, M Andrew; Schweitzer, Robert L (Journal of Finance, 1990)
This study examines the impact on shareholder wealth of changes in interstate banking laws. The research demonstrates that changes in state statutes that allow interstate banking have a positive impact on the stock prices of regional banking organizations and a negative impact on the stock prices of money center banks. Interstate banking statutes initially exclude those states in which the money center banks are headquartered. The findings provide evidence that, by excluding money center banks from expansion across state lines, the competition from the regional banks may have an adverse competitive effect on the money center banks.